2000
DOI: 10.1063/1.1311954
|View full text |Cite
|
Sign up to set email alerts
|

Using convective flow splitting for the direct printing of fine copper lines

Abstract: Liquid ribbons of solutions of copper hexanoate in a volatile solvent were drawn on a glass slide using either fine glass capillaries or an ink jet printer. After solvent evaporation, the solute was observed to segregate into multiple pairs of stripes much narrower than the initial ribbon diameter. These stripes were then converted to pure copper by annealing. Surface profiles indicate that the thickness, width, and number of lines formed are strongly dependent on the solution viscosity and volume per unit len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
61
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 22 publications
1
61
0
Order By: Relevance
“…The emergence of cost-effective microfluidic devices allowing manipulation and control of fluids on micrometer scales has promised a significant new paradigm for the manufacturing industry [1,2]. Known as bottom-up processing, the required material can be transported to its destination in solvent form and deposited onto the target substrate using established technologies such as ink-jet head fluid ejection.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of cost-effective microfluidic devices allowing manipulation and control of fluids on micrometer scales has promised a significant new paradigm for the manufacturing industry [1,2]. Known as bottom-up processing, the required material can be transported to its destination in solvent form and deposited onto the target substrate using established technologies such as ink-jet head fluid ejection.…”
Section: Introductionmentioning
confidence: 99%
“…The evaporation of a solvent and solute has important consequences, such as the generation of internal flow, contact-angle change, 1 DNA stretching, [2][3][4][5] and particle adsorption at the three-phase contact line for particle-laden fluids. [6][7][8][9][10][11][12] In addition, the evaporation of a sessile droplet has various practical applications. These include the spray cooling process, 2,13 DNA stretching, 3-5, 7, 14 thin film deposition, [15][16][17][18][19] and the fabrication of patterned surfaces inspired by the coffee-stain phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…These include the spray cooling process, 2,13 DNA stretching, 3-5, 7, 14 thin film deposition, [15][16][17][18][19] and the fabrication of patterned surfaces inspired by the coffee-stain phenomenon. [20][21][22] This fabrication of patterned surfaces has various applications such as DNA/RNA microarrays, 23,24 ordering and assembling of colloidal particles by evaporation, 6,8,25,26 fabrication of microlenses, 1,27,28 and electronic devices fabricated by the ink-jet printing method. 5,[29][30][31] Several kinds of fluid flow are autonomously generated inside an evaporating droplet.…”
Section: Introductionmentioning
confidence: 99%
“…Besides conductive polymers, inks that contain metals have been used to create microstructures on polymer substrates (Smith et al, 2006;Kim et al, 2007). It has been shown that inkjet printing of conductive materials is a relatively cheap alternative for the fabrication of electronic devices when compared to other micro-and nanopatterning techniques (Menard et al, 2007), such as photo-lithography (Liu et al, 2005) or laser patterning (Cuk et al, 2000).…”
Section: Introductionmentioning
confidence: 99%